Tinjauan Fatwa DSN MUI No: 145/DSN-MUI/XII/2021 terhadap Implementasi Jual Beli Online Sistem Dropship pada Toko Tiens Bandung - Rivany Rida Firdaus; Nandang Ihwanudin; Muhammad Yunus (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Dropshippers in their marketing are required to provide clear, honest and trustworthy product descriptions. Islam gives freedom for the parties to continue or cancel a transaction if there is an element of disability in it, in this case it is commonly referred to as khiyar rights. This study aims to analyze buying and selling practices carried out by dropshippers from Toko Tiens Bandung in marketing products on social media, as well as reviewing DSN MUI Fatwa No: 145/DSN-MUI/XII/2021 regarding online buying and selling practices. The method used in this study is a qualitative descriptive analysis research with a normative approach, where the data collection is through interviews. This research can be concluded 1) The practice of buying and selling online in marketing is carried out by dropshippers by uploading product images and product descriptions. The product description uploaded by the dropshipper looks exaggerated because when consumers complain about inappropriate products, the dropshipper cannot be held accountable for what is stated in the description uploaded. 2) Review of DSN MUI Fatwa No: 145/DSN-MUI/XII/2021 regarding the practice of buying and selling online by dropshippers from the Tiens Bandung store is still not fully in accordance with the fatwa. In practice, dropshippers do marketing by exaggerating sentences in uploaded product descriptions to impress consumers to buy products. Dropshippers have also not implemented khiyar rights to buyers, either in the form of refunds or returns. This is not in accordance with the contents of the fatwa in point 4 point 5, point 7 point 6. Abstrak. Dropshipper dalam pemasarannya, dituntut untuk memberikan deskripsi produk secara jelas, jujur, dan amanah. Islam memberikan kebebasan bagi para pihak untuk meneruskan atau membatalkan suatu transaksi bila didalamnya terdapat unsur kecacatan, dalam hal ini biasa disebut sebagai hak khiyar. Penelitian ini bertujuan untuk menganalisis praktik jual beli yang dilakukan oleh dropshipper Toko Tiens Bandung dalam memasarkan produk di media sosial, serta meninjau Fatwa DSN MUI No: 145/DSN-MUI/XII/2021 terhadap praktik jual beli. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif analisis deskritif dengan pendekatan normatif, dimana dalam pengumpulan data melalui wawancara. Penelitian ini dapat ditarik kesimpulan 1) Praktik jual beli online dalam pemasaran yang dilakukan dropshipper dengan mengunggah gambar produk dan deskripsi produk. Deskripsi produk yang diunggah oleh dropshipper terlihat dilebih-lebihkan karena pada saat konsumen komplain terhadap produk yang tidak sesuai, dropshipper tidak dapat mempertanggungjawabkan sesuai apa yang tercantum pada deskripsi yang diunggahnya. 2) Tinjauan Fatwa DSN MUI No: 145/DSN-MUI/XII/2021 terhadap praktik jual beli online oleh dropshipper toko Tiens Bandung masih belum sepenuhnya sesuai dengan fatwa. Pada praktiknya, dropshipper melakukan pemasaran dengan melebih-lebihkan kalimat pada deskripsi produk yang diunggah agar menimbulkan kesan pada konsumen untuk membeli produk. Dropshipper juga belum menerapkan hak khiyar kepada pembeli, baik dalam bentuk refund ataupun return. Hal tersebut tidak sesuai dengan isi fatwa dalam butir 4 point ke-5 dan butir 7 point ke-6.